Study of Human Resources Management in the Development of Pawn Application Startup Companies Using SWOT Analysis - Padsha Dirgantara; Edi Hamdi (Syntax Corporation Indonesia, 2023)
This writing aims for knowing how to plan strategy source power humans do by company application startup pawn private owned competence in the field of information technology. Then inside this writing in the analysis is source power existing humans effective or no. Type writing research that was carried out characteristic descriptive analyst, that is research that describes the planning strategy source power man in effort Upgrade performance employee. Data collection is done with observation and documentation. Data analysis techniques using analysis descriptive combined qualitative _ with approach SWOT analysis. Results writing explain that in planning source power man there is a number of stages in process procurement employee new. And deep operate activity the company's operations consider strengths, weaknesses, opportunities, and threats that a moment could profitable and detrimental company.